Tauhid is the Main Solution to Overcoming the Covid-19 Pandemic - Monang, Sori; Saputra, Bambang; Harahap, Abdurrohim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Covid-19 has changed the world order. The number of victims of COVID-19 is increasing day by day. According to the latest figures from the World Health Organization (WHO) Friday (20/07) the number of Covid-19 cases worldwide reached 90,054,813. Various efforts in the context of prevention, treatment, and so on have also been made to prevent the spread of the corona virus, to lockdown and social distancing. However, as a religious community (Islam) the Covid-19 pandemic has actually become an opportunity to increase tauhid to Allah SWT. From the point of view of Islam, the Corona virus outbreak can be seen as a test for a people to always draw closer to Allah. Using the content analysis methodology, this study seeks to link tauhid with the prevention of the COVID-19 pandemic. As a Muslim, we are required to realize tauhid in our daily lives, because tauhid is the basic teaching of Islam on which religious laws are built. The conclusion obtained is that increasing tauhid will be able to prevent the transmission of covid-19 through a strong belief that Allah SWT will take care of His servants who always maintain cleanliness by ablution and also believe in Allah SWT as a healing god (positive thinking) so that it can increase the immunity of the human body.